Earthquake‐related temperature changes in two neighboring hot springs at Xiangcheng, China. Issue 3 (22nd October 2015) - Ma, Y.
Abstract: Pre‐earthquake and postearthquake temperature changes were documented in two hot springs at Xiangcheng. Pre‐earthquake changes were documented in spring I, 13 days before and 106 km away from the M s 5.8 Zhongdian earthquake. The 11‐year cutoff spring spouted again, and the spouted water was 24°C hotter than the former escaping gas. Postearthquake changes were documented in spring II following the 2008 M w 7.9 Wenchuan earthquake, approximately 425 km away from the epicenter. Temperature in spring II showed a step‐like increase with a magnitude of 4°C induced by the earthquake. Spring I which is 0.3 m apart from spring II did not show a sudden change following the earthquake. However, temperatures in the two springs were identical after the Wenchuan earthquake. It indicates that the earthquake generated new hydraulic connectivity between springs I and II, and the heat transport between the two springs accounts for the postearthquake temperature changes.